2019
DOI: 10.1073/pnas.1902781116
|View full text |Cite
|
Sign up to set email alerts
|

Otogelin, otogelin-like, and stereocilin form links connecting outer hair cell stereocilia to each other and the tectorial membrane

Abstract: The function of outer hair cells (OHCs), the mechanical actuators of the cochlea, involves the anchoring of their tallest stereocilia in the tectorial membrane (TM), an acellular structure overlying the sensory epithelium. Otogelin and otogelin-like are TM proteins related to secreted epithelial mucins. Defects in either cause the DFNB18B and DFNB84B genetic forms of deafness, respectively, both characterized by congenital mild-to-moderate hearing impairment. We show here that mutant mice lacking otogelin or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…At its medial edge, the TM is anchored to the apical surface of the epithelium via the GPI-anchored protein otoancorin; at its lower lateral edge, the TM contacts the apical stereocilia of three rows of sensorimotor outer hair cells (OHCs). Recent genetic and morphological analysis has revealed that otogelin, otogelin-like, and the membrane-anchored stereocilin play interrelated roles in connecting the tips of OHC stereocilia to the TM 46 . While otogelin, otogelin-like, and stereocilin all localize independently within OHC hair bundles, loss of any one protein disrupts the distribution of the other two, suggesting interdependent roles in TM-OHC attachment.…”
Section: Patterning the Aecm Of The Vertebrate Inner Earmentioning
confidence: 99%
“…At its medial edge, the TM is anchored to the apical surface of the epithelium via the GPI-anchored protein otoancorin; at its lower lateral edge, the TM contacts the apical stereocilia of three rows of sensorimotor outer hair cells (OHCs). Recent genetic and morphological analysis has revealed that otogelin, otogelin-like, and the membrane-anchored stereocilin play interrelated roles in connecting the tips of OHC stereocilia to the TM 46 . While otogelin, otogelin-like, and stereocilin all localize independently within OHC hair bundles, loss of any one protein disrupts the distribution of the other two, suggesting interdependent roles in TM-OHC attachment.…”
Section: Patterning the Aecm Of The Vertebrate Inner Earmentioning
confidence: 99%
“…Finally, the presence of both L-whirlin and the PCDH15 isoforms CD1 and CD2 at the tips of the tall stereocilia, and their physical interaction demonstrated here in vitro, raises the possibility that L-whirlin might be required to anchor a subpopulation of apical lateral links containing PCDH15 or CDH23 to the actin cores of these stereocilia. Indeed, the top-connector-associated proteins stereocilin, otogelin and otogelin-like have an abnormally extended distribution in the absence of PCDH15 or CDH23 17 . Accordingly, the impaired DPOAEs and frequency tuning in mutant mice lacking the L-whirlin isoform could reflect a loosening of the OHC hair bundle cohesiveness due to the loss of these apical lateral links, since the loss of OHC bundle cohesiveness abolishes DPOAEs, as occurs in stereocilin-null mutant mice which lack the top-connectors 16,17,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the top-connector-associated proteins stereocilin, otogelin and otogelin-like have an abnormally extended distribution in the absence of PCDH15 or CDH23 17 . Accordingly, the impaired DPOAEs and frequency tuning in mutant mice lacking the L-whirlin isoform could reflect a loosening of the OHC hair bundle cohesiveness due to the loss of these apical lateral links, since the loss of OHC bundle cohesiveness abolishes DPOAEs, as occurs in stereocilin-null mutant mice which lack the top-connectors 16 , 17 , 50 .
Figure 5 L-whirlin-interacting networks at the ankle-links and at stereocilia tips.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereocilia are cross-linked by a number of transient or permanent links, collectively termed as stereociliary 'surface specializations' , which are identified with electron microscopy and ensure bundle integrity 1 . A list of proteins were shown to be important for the hair cell stereocilia bundle structure and function, many of which were localized to the bundle using variations of immunogold labeling protocols, and observed with electron microscopy (EM) techniques, mostly using transmission electron microscopy (TEM) [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and more lately using scanning electron microscopy (SEM) [16][17][18][19][20][21] . In the most recent years though, serial electron microscopy techniques have become more accessible for use in biology, mounting a new body of work using 3D EM approaches 17,22,23 .…”
Section: Background and Summarymentioning
confidence: 99%